(untitled) (مجلة الواحات للبحوث والدراسات, 2017)
The research aims to discuss the problematic use of genetic fingerprint in the denial of genealogy, and its relation with the curse, and seeks to answer the question about the possibility of erasing effects of descent between who ask a curse and the child – which was main by the old scholars after a curse. In light of what they produce genetic fingerprint, and related to the difference between the modern scholars and Algerian legislation, and what the judge must do when it is adjucated in the cases of the curse if the genetic fingerprint is supportive of the side of the husband who ask curse. Key words - Descent- Genetic fingerprint- Islamic fiqh- Algerian legislation- Comparative . مقدمة-